THE COMPREHENSION OF CHEMISTRY TEACHER TOWARD STEM INTEGRATION IN CHEMISTRY LEARNING - Hafsah Thaha; Nur Fitriyana; Fapriyan Mulyopratikno (Universitas Negeri Yogyakarta, 2021)
This study was aimed to investigate the chemistry teacher knowledge related STEM integration in chemistry learning at automotive engineering programme of vocational school This research belonged to descriptive study with survey methods. The samples consisted of 19 ChTAE at automotive vocational school in Bantul Regency, Indonesia that were established through saturated sampling technique. The preceding knowledge about the IC-STEM learning integration of ChTAE were achieved by using STEM Knowledge Questionnaire (STEM-KQ) consisting of 9 opened questions. The responses of ChTAE toward STEM-KQ were analysed using question-by-question with interpretative coding of content analysis. The results of this research indicate that the ChTAE have good knowledge in defining and explaining STEM which in line with chemistry subject. However, their skills in designing and implementing CI-STEM still need to be enhanced. As the matter of that, the ChTAE must follow the activities relating with the preparation of CI-STEM. Therefore, the ChTAE could implement a meaningful chemistry subject in line with automotive expertise programme at vocational school.